Pembuatan Sistem Kontrol Otomatis pada Mesin Press Plastik Berbasis PLC di PT. Laksana Teknik Makmur - Lin Prasetyani (Universitas Halu Oleo, 2022)
Laksana Tekhnik Makmur Tbk. is a manufacturing company that produces marine interiors and automotive accessories. The company usually uses a continuous sealer machine for plastic production processes. The continuous sealer machine is a plastic press machine that can automatically glue plastic packaging and aluminum foil. The plastic press process on this continuous sealer machine requires three persons as the operator and four work steps, namely, pressing the bottom plastic, installing the iron clip on the top, pressing the plastic on the top, and removing the iron clip. In these work steps, the plastic sealer press process is carried out twice in a product. These steps waste time and operator cause the plastic press process is inefficient. The problem from a continuous sealer machine was replaced by making an automatic control system on the plastic hot press machine. This machine will reduce the number of working steps from four working steps to two working steps. So that it can reduce the cycle time by 75% and increase the production of plastic presses by 24,000 pcs a day.